Ballistic Reconstruction of a Migrating Bullet in the Parapharyngeal Space. (7th December 2015) - Bächinger, David; Bolliger, Stephan; Huber, Gerhard F.; Laske, Roman D.
Abstract : A 21-year-old male suffering from severe throat pain after being hit by a bullet in Syria claimed that he was shot through his eye and that the bullet subsequently descended behind his throat. Even though the first medical report stated that this course is implausible, meticulous workup provided evidence that the bullet might have entered the parapharyngeal space in a more cranial position than the one it was found eight months later. Our case highlights that bullets are able to move within the body, rendering ballistic reconstruction difficult. However, after removal of the bullet the patient's symptoms completely resolved.